ENHANCING PARAGRAPH WRITING AMONG NINTH-GRADE STUDENTS THROUGH THE COMPLETE-SENTENCE MODEL: A PRETEST–POSTTEST STUDY - Rahmadsyah Lubis; Nisrina Nurhaliza; Sri Handayani Siregar; Eni Fauziah Harahap; Mirjam Anugerahwati (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study investigated the effectiveness of the Complete‑Sentence Model in enhancing paragraph‑writing ability among ninth‑grade students at SMP Negeri 2 Sibabangun. Specifically, it aimed to (1) describe the implementation of the Complete‑Sentence Model in teaching paragraph writing, (2) measure students’ paragraph‑writing ability before and after the intervention, and (3) determine whether the model produced a statistically significant improvement. A pre‑experimental one‑group pretest–posttest design was employed. The population was all Grade IX students (N = 84); a purposive sample of 29 students from class IX C participated. Data were collected via observation checklists and writing tests. Findings show that implementation quality was rated as good (mean = 3.4). Students’ mean writing score improved markedly from 39 (pretest; fail) to 75 (posttest; good). A paired t‑test confirmed the improvement was statistically significant (t = 11.78 > tcritical = 2.05), leading to acceptance of the hypothesis. The results indicate that the Complete‑Sentence Model is an effective instructional strategy for improving paragraph‑writing ability among ninth‑grade students at the study site.